Incidence of incidental carcinoma gall bladder in cases of routine cholecystectomy - Ghimire, P; Yogi, N; Shrestha, B B (Kathmandu University Medical Journal, 2012)
Background Carcinoma of gall bladder is the most common malignancy of the billiary tract. Most of the cases are diagnosed as an incidental case among patients undergoing cholecystectomy. Objectives To establish the rate of incidental carcinoma of gall bladder in patients undergoing routine cholecystectomy to study the demographic profile and prognosis of these patients. Methods A retrospective study was carried out in Fishtail Hospital and Research Center, Pokhara during 1998-2009. The surgical notes, hospital records and histopathology reports of 783 patients undergoing routine cholecystectomy were studied. Results Out of 783 cases, gall bladder cancer was detected in 10(1.28%) of cases and was more common in females (M:F ratio 1:2.3) and the mean age of occurrence was 63.8 years. Most of the cases diagnosed were at their early stages and none of them were in T3 and T4 stages. Six of these patients have survived till a mean follow up duration of 23.7 months. Conclusion The rate of incidental carcinoma of gall bladder is 1.28%. DOI: http://dx.doi.org/10.3126/kumj.v9i2.6278 Kathmandu Univ Med J 2011;9(2):3-6